2009
DOI: 10.1007/s11270-009-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biodegradation of Used Engine Oil in Soil Amended with Organic Wastes

Abstract: Three organic wastes (banana skin (BS), brewery spent grain (BSG), and spent mushroom compost (SMC)) were used for bioremediation of soil spiked with used engine oil to determine the potential of these organic wastes in enhancing biodegradation of used oil in soil. The rates of biodegradation of the oil were studied for a period of 84 days under laboratory conditions. Hydrocarbon-utilizing bacterial counts were high in all the organic waste-amended soil ranging between 10.2×10 6 and 80.5×10 6 CFU/g compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
51
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 31 publications
11
51
3
Order By: Relevance
“…Organic wastes like banana skin, spent mushroom compost and brewery spent grain in earlier studies were found to enhance the biodegradation of used lubricating oil up to 90% loss of oil within the period of 3 months (Abioye, et al, 2009b(Abioye, et al, , 2010. Also the results of our studies revealed the potential of melon shell to stimulate 75% crude oil degradation in soil contaminated with crude oil within the period of 28 days (Abioye, et al, 2009a). Depending on the nature of the contaminated soil, some of these nutrients could become limiting, hence the additions of nutrients are necessary to enhance the biodegradation of oil pollutants (Choi et al, 2002;Kim et al, 2005).…”
Section: Biostimulationsupporting
confidence: 63%
“…Organic wastes like banana skin, spent mushroom compost and brewery spent grain in earlier studies were found to enhance the biodegradation of used lubricating oil up to 90% loss of oil within the period of 3 months (Abioye, et al, 2009b(Abioye, et al, , 2010. Also the results of our studies revealed the potential of melon shell to stimulate 75% crude oil degradation in soil contaminated with crude oil within the period of 28 days (Abioye, et al, 2009a). Depending on the nature of the contaminated soil, some of these nutrients could become limiting, hence the additions of nutrients are necessary to enhance the biodegradation of oil pollutants (Choi et al, 2002;Kim et al, 2005).…”
Section: Biostimulationsupporting
confidence: 63%
“…1 , Ganiyu K. Latinwo 1 soil remediation includes mechanical, burying, evaporation, dispersion, and washing. However, these technologies are expensive and can lead to incomplete decomposition of contaminants [Das and Chandra, 2011].…”
Section: Samuel Agarrymentioning
confidence: 99%
“…Moreover, as plants reside at the lower ranks in the food chain, their bioaccumulation can lead to severe toxicity in tertiary consumers, including humans [8][9]. Therefore, once entered in the human bodies through the food chain, many of these compounds can result in renal disorders, liver diseases, and alteration in DNA [1,10]. Besides, the presence of EEO in soil can also disturb soil ecology, soil fertility, and alteration of soil structure leading to crop contamination [11].…”
mentioning
confidence: 99%